Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1159/000171480
|View full text |Cite
|
Sign up to set email alerts
|

Word Recognition following Implantation of Conventional and 10-mm Hybrid Electrodes

Abstract: We compared the effectiveness of 2 surgical interventions for improving word recognition ability in a quiet environment among patients who presented with: (1) bilateral, precipitously sloping, high-frequency hearing loss; (2) relatively good auditory thresholds at and below 500 Hz, and (3) poor speech recognition. In 1 intervention (n = 25), a conventional electrode array was inserted into 1 cochlea. As a consequence, hearing was lost in the implanted ear. In the other intervention (n = 22), a Nucleus Hybrid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…There are different EAS designs that have been implemented by multiple cochlear implant manufacturers (e.g., Cochlear Corporation and MED-EL) over the past ten years, all with the same goal to preserve acoustic hearing in the low-frequencies while providing high-frequency speech and sound perception by electrically stimulating the basal region of the cochlea. Research has shown that speech perception scores using EAS can be similar to those obtained with long-electrode CIs (Gstoettner et al, 2006; Reiss et al, 2008, Dorman et al, 2009). A further advantage of EAS is that by preserving residual low-frequency hearing, frequency resolution is improved as evidenced by improved music perception abilities and better speech perception in background babble compared to electric stimulation alone (Turner et al, 2004; Helbig et al, 2008; Lorens et al, 2008; Dorman and Gifford, 2010; Gfeller et al, 2006).…”
Section: Introductionmentioning
confidence: 72%
“…There are different EAS designs that have been implemented by multiple cochlear implant manufacturers (e.g., Cochlear Corporation and MED-EL) over the past ten years, all with the same goal to preserve acoustic hearing in the low-frequencies while providing high-frequency speech and sound perception by electrically stimulating the basal region of the cochlea. Research has shown that speech perception scores using EAS can be similar to those obtained with long-electrode CIs (Gstoettner et al, 2006; Reiss et al, 2008, Dorman et al, 2009). A further advantage of EAS is that by preserving residual low-frequency hearing, frequency resolution is improved as evidenced by improved music perception abilities and better speech perception in background babble compared to electric stimulation alone (Turner et al, 2004; Helbig et al, 2008; Lorens et al, 2008; Dorman and Gifford, 2010; Gfeller et al, 2006).…”
Section: Introductionmentioning
confidence: 72%
“…Based on data from the literature [Dorman et al, 2003[Dorman et al, , 2009Fitzgerald et al, 2008], the effectiveness of electric stimulation, specifically the individual's ability to recognize pitch and speech, increased with the number of active intracochlear electrodes and the insertion depth. Other investigations clearly demonstrated the strong impact of the apical region of the cochlea on speech perception [Hochmair et al, 2003;Hamzavi and Arnoldner, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…However, the functional results of a 6-mm implantation were not sufficient for speech recognition and clearly improved after subjects received a 10-mm insertion [Gantz and Turner, 2003;Turner et al, 2004]. Even a 10-mm implant may have a limited effect on speech understanding compared with a longer electrode [Dorman et al, 2005[Dorman et al, , 2007[Dorman et al, , 2009Fitzgerald et al, 2008] when considering individuals with complete or progressive hearing loss and/ or those with poor acoustic hearing preoperatively [Dorman et al, 2003], so that in case of failure a secondary implantation with a deep insertion is deemed necessary. More recently, a 16-mm implantation depth was advocated as a compromise .…”
Section: Insertion Depthmentioning
confidence: 99%
“…Shallop et al, 1992; Armstrong et al, 1997; Tyler et al, 2002; Ching et al, 2004; Gantz & Turner, 2004; Gstoettner et al, 2004; Kiefer et al, 2004; Turner et al, 2004; Kong et al, 2005; Gifford et al, 2007; Dorman et al, 2008, 2009; Mok et al, 2006). Here we describe the results from two of our recent studies.…”
Section: What Level Of Performance Can Be Achieved With Eas?mentioning
confidence: 99%